Psychological Assessment and Psychological First Aid Psychoeducation to Enhance Fundamental Knowledge in Assisting Disaster Survivors to Pusat Pengendalian Operasi Penanggulangan Bencana Kabupaten Garut - Noura, Athiya; Wardhani, Nurul; Kumalasari, Asteria Devy; Abidin, Fitri Ariyanti (Dinasti International Journal of Education Management and Social Science, 2025)
Kabupaten Garut is an area with a high level of disaster vulnerability, causing communities to frequently experience both physical and psychological impacts in the aftermath of disasters. On the other hand, the effectiveness of the Pusdalops PB BPBD Garut response remains limited due to the placement of members that do not yet align with their personality characteristics, as well as insufficient psychosocial capacity when dealing directly with survivors. To address these issues, this intervention was designed using two approaches: a DISC personality assessment to allocate members into four work clusters (logistics, decision-makers, communicators, and data assessors), and Psychological First Aid (PFA) psychoeducation to enhance knowledge and self-efficacy. The program involved 23 participants through DISC assessment, PFA training, and a pretest–posttest evaluation using the Wilcoxon test. The results showed significant improvements across all variables, including PFA knowledge (Z = –3.649; p = 0.000), self-efficacy in responding to survivors (Z = –2.496; p = 0.013), self-efficacy in recognising survivors (Z = –2.858; p = 0.004), and emotional regulation self-efficacy (Z = –2.550; p = 0.011). These findings highlight that personality-based role placement and PFA psychoeducation are effective in strengthening psychosocial preparedness and can serve as a relevant intervention model for disaster-prone regions such as Kabupaten Garut.